Measurement and evaluation in human performance - Morrow, J. R.; Mood, D. P.; Disch, J. G.; Kang, M. (Human Kinetics, 2016)
Measurement and Evaluation in Human Performance, Fifth Edition With Web Study Guide, leads students through the fundamentals of collecting and analyzing data of human performance and applying their results to real-life situations. Focusing on the core concepts of reliability and validity of data, the text provides all the necessary tools for evidence-based decision making that can be applied to physical therapy, allied health professions, kinesiology, sport and exercise science, physical education, health, and fitness.